2021
DOI: 10.1007/s13555-021-00575-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Platelet-Rich Plasma in Melasma: A Systematic Review and Meta-Analysis

Abstract: Introduction: Melasma is a chronic and recurrent skin problem for which an effective therapy is currently lacking. Platelet-rich plasma (PRP) has recently emerged as a novel treatment for melasma, but to date there has been no systematic evaluation of its efficacy and safety. Methods: The Web of Science, PubMed, EMBASE, China National Knowledge Infrastructure (CNKI) and the Cochrane Library databases were searched for relevant articles using the search items ''melasma,'' ''chloasma'' and ''platelet-rich plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Interestingly, a recent study has shown that, compared to the use of microneedling alone, combined treatment with microneedling and PRP was associated with a marked excellent improvement of the skin lesions, a more significant deposition of collagen and elastic fibers, and an increased proliferative activity in the epidermis in people with striae distensa, which may also reflect the synergetic benefits of action microneedling and PRP on scar formation and collagen/dermal remodeling ( 40 ). Interestingly, the efficacy of combined treatment with microneedling and PRP has also been observed in people with androgenetic alopecia ( 41 ) and melisma ( 42 ). The exact molecular mechanisms underlying the benefits of a combined therapy with microneedling and PRP for atrophic acne scars should be further evaluated.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, a recent study has shown that, compared to the use of microneedling alone, combined treatment with microneedling and PRP was associated with a marked excellent improvement of the skin lesions, a more significant deposition of collagen and elastic fibers, and an increased proliferative activity in the epidermis in people with striae distensa, which may also reflect the synergetic benefits of action microneedling and PRP on scar formation and collagen/dermal remodeling ( 40 ). Interestingly, the efficacy of combined treatment with microneedling and PRP has also been observed in people with androgenetic alopecia ( 41 ) and melisma ( 42 ). The exact molecular mechanisms underlying the benefits of a combined therapy with microneedling and PRP for atrophic acne scars should be further evaluated.…”
Section: Discussionmentioning
confidence: 95%
“…The safety, efficacy, and prognosis of PRP have not been fully confirmed. Zhao et al [ 12 ] recently reported a systematic review on PRP in the treatment of chloasma, which included studies without controlled experimental designs. We will elaborate on the application of PRP in chloasma under more stringent inclusion and exclusion criteria and bias evaluation and try to explore the evaluation of efficacy and safety by multiple factors including ethnic differences and pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the direct effect of PRP on cell proliferation, migration, cell differentiation and angiogenesis, PRP also affects tissue regeneration and local control of inflammatory conditions. TGF‐β1 in PRP delays activation of extracellular signal‐regulated kinase thus inhibiting melanin synthesis 14 . In addition, PDGF in PRP may help in increasing the skin volume by angiogenesis, collagen synthesis, and extracellular matrix formation that result in reduced pigmentation and skin luster, elasticity and improvement in cosmetic appearance 13,15,16 …”
Section: Introductionmentioning
confidence: 99%
“…3,13 Some of the growth factors released by platelets in PRP are platelet-derived growth factor (PDGF), epithelial growth factor (EGF), vascular endothelial growth factor (VEGF), endothelial cell growth factor (ECGF), fibroblast growth factor (FGF), transforming growth factor beta (TGF-β), and insulin-like growth factor (IGF). 14,15 In addition to the direct effect of PRP on cell proliferation, migration, cell differentiation and angiogenesis, PRP also affects tissue regeneration and local control of inflammatory conditions. TGF-β1 in PRP delays activation of extracellular signal-regulated kinase thus inhibiting melanin synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation